Wind tunnel experiment on rectangular-shaped arch-supported membrane structures. (July 2022) - Kandel, Arjun; Sun, Xiaoying; Wu, Yue
Abstract: This paper highlights the investigation of wind tunnel experiment on rectangular-shaped arch-supported membrane structures. Series of wind tunnel experiments are carried out to record the time history of pressure under different wind directions for both enclosed and open structures. In order to present the comparative analysis, contours and graphs for mean and peak wind pressure coefficients are plotted considering different parameters such as rise-span ratio, wind direction, and boundary wall. Study shows that under oblique wind direction, strong flow separation occurs in the windward arch edge which creates larger suction pressure coefficient on the immediate downside of windward arch. Based on area and intensity of negative pressure coefficient, 45⁰ is the most critical wind direction. Influence of rise-span ratio is noticeable. When rise-span ratio increases from 0.2 to 0.35, pressure coefficient increases significantly, however when rise-span ratio further increases to 0.5, increase in pressure coefficient is marginal. Moreover, in order to ease the engineering design application, roof surface is divided into different zones and assigned with mean and peak wind pressure coefficient.